TEACHING THE INDONESIAN LANGUAGE IN PRIMARY SCHOOLS: A LITERATURE REVIEW ON STRATEGIES AND CHALLENGES - Destiara Andini Ulandari (CV. Fahr Publishing, 2025)
This study aims to explore and synthesize the strategies and challenges in teaching the Indonesian language at the primary school level through a systematic literature review method. Drawing upon selected empirical and theoretical sources published between 2020 and 2025, the review critically examines various instructional approaches, including contextual teaching, literacy-based media, interactive reading aloud, and technology-enhanced learning, within the framework of the Kurikulum Merdeka. The data were collected from reputable academic databases using structured search criteria and analyzed thematically. The findings reveal that while several innovative strategies have proven effective—particularly in enhancing literacy, engagement, and communication skills—numerous challenges persist, such as limited teacher training, inadequate teaching materials, and the linguistic diversity of students. The novelty of this research lies in its integrative analysis, which combines pedagogical models with contextual variables (e.g., urban-rural divide, multilingual classrooms) and policy shifts, offering a more comprehensive perspective than previous reviews. It also highlights under-researched areas and underscores the importance of aligning strategy implementation with teacher competence and local school conditions. In conclusion, the study provides a holistic view of Indonesian language instruction at the elementary level and emphasizes the need for systemic support, especially in under-resourced environments. These insights are valuable not only for Indonesian educators and policymakers but also for other multilingual education systems seeking effective models of primary language instruction.